Deepfakes: Deceptions, mitigations, and opportunities - Mustak, Mekhail; Salminen, Joni; Mäntymäki, Matti; Rahman, Arafat; Dwivedi, Yogesh K. (Elsevier, 2022)
Deepfakes—artificial but hyper-realistic video, audio, and images created by algorithms—are one of the latest technological developments in artificial intelligence. Amplified by the speed and scope of social media, they can quickly reach millions of people and result in a wide range of marketplace deceptions. However, extant understandings of deepfakes’ implications in the marketplace are limited and fragmented. Against this background, we develop insights into the significance of deepfakes for firms and consumers—the threats they pose, how to mitigate those threats, and the opportunities they present. Our findings indicate that the main risks to firms include damage to image, reputation, and trustworthiness and the rapid obsolescence of existing technologies. However, consumers may also suffer blackmail, bullying, defamation, harassment, identity theft, intimidation, and revenge porn. We then accumulate and present knowledge on the strategies and mechanisms to safeguard against deepfake-based marketplace deception. Furthermore, we uncover and report the various legitimate opportunities offered by this new technology. Finally, we present an agenda for future research in this emergent and highly critical area.
Keywords: Deception; Deepfake; Fake photo; Fake video; Machine learning; Threats; Challenges; Opportunities; Protection; marketing; artificial intelligence; fi=Markkinointi|en=Marketing|